The Potential Economic Impact of the India-Pakistan Conflict on Indonesia: A Growing Threat to Stability and Growth - A. Junaedi Karso (International Forum of Researchers and Lecturers, 2025)
The potential war between India and Pakistan poses significant risks to the Indonesian economy, as it is expected to exacerbate uncertainty in the global financial market. Such geopolitical tensions often trigger a ‘flight to safety,’ where capital flows shift to countries considered stable, leading to reduced foreign direct investment (FDI) in emerging markets like Indonesia. This scenario is likely to place additional pressure on Indonesia’s exchange rate, further destabilizing its financial position. One of the key impacts of the looming India-Pakistan war on Indonesia is its effect on monetary and fiscal management. The Indonesian government is already facing significant challenges, including managing a large amount of maturing debt and grappling with a growing budget deficit. The war would complicate these efforts, making it more difficult for the government to stabilize the economy and implement effective policies. Indonesia’s export sector will also be affected, as India and Pakistan are two of the country’s main trading partners, especially for key commodities like crude palm oil (CPO) and coal. India is Indonesia’s 4th largest export destination, accounting for approximately 9% of total exports, while Pakistan represents around 1.9%. Any disruption in trade with these countries, due to the war or political instability, could significantly hurt Indonesia’s export revenues and negatively affect industries reliant on these markets. Moreover, Indonesia is already facing challenges from the United States, which has imposed reciprocal tariffs worth 32% on Indonesian products. This trade tension, combined with the geopolitical instability from the India-Pakistan conflict, will add further strain to Indonesia’s trade balance. The combination of these factors could lead to slower economic growth, reduced investor confidence, and potentially higher inflation, as the country faces multiple external and internal economic pressures.